Analysis of Distribution Channels For MSMEs Pindang Fish (CUE) - Suhada, Muhammad; fadli, Uus MD; Khalida, Laras Ratu (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine the distribution pattern of pindang fish in North Cicinde, Banyusari Sub-district, Karawang Regency at the household (micro), small and medium scale businesses. This research used descriptive methods. Primary data were obtained through interviews with informants / pindang fish entrepreneurs at the household, small and medium scale. Data analysis was carried out descriptively. The results of the study are the distribution of pindang fish in two types, namely direct distribution called zero-level channels (0-Level) carried out by household scale businesses (micro) and small, marketing through intermediaries is in the form of the first channel called a three-level channel (3-Level) carried out by household scale businesses and small; the second channel form is called a one-level channel (1-Level) carried out by household scale businesses (micro) and small; the third channel form is called a two-level channel (2-Level) carried out by pindang fish entrepreneurs with medium scale businesses.